Hypoxia formation in the East China Sea by decomposed organic matter in the Kuroshio Subsurface Water. (April 2022) - Wang, Wentao; Yu, Zhiming; Song, Xiuxian; Chi, Lianbao; Zhou, Peng; Wu, Zaixing; Yuan, Yongquan
Abstract: Although internal decomposition of organic matter (OM) in the Kuroshio Subsurface Water (KSSW) is a crucial factor for hypoxia formation in the East China Sea (ECS), the seasonal source and contributions of this OM remain debated. This study applied datasets collected in June and October 2015 to discuss these issues qualitatively and quantitatively. According to the variations in several parameters along the KSSW route, N2 fixation signals related to decomposed OM were apparent in the southern ECS during June, while terrestrial input signals were revealed in the northern ECS during June and most of the ECS during October. The terrestrial input contributed 47% of the decomposed OM near the historic hypoxic area in June, indicating that the terrestrial and marine sources contributed almost equally to the development of ECS hypoxia. These results provide vital information for understanding the mechanism of hypoxia formation driven by eutrophication and oceanic circulation. Graphical abstract: Unlabelled Image Highlights: OM decomposition consumes DO seasonally in high salinity waters on the ECS shelf. N2 fixation introduced newly fixed nitrogen during June in the southern ECS. Nitrogen remineralization was dominant during October or near the CRE. Riverine and oceanic nitrogen contributed equally to ECS hypoxia.